Ability of low profile cross-ventilated freestall barns to improve environmental conditions for dairy cattle - Smith, John F., 1962-; Harner, Joseph P.; Brouk, Michael J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Recently, there has been interest in constructing mechanical ventilation with evaporative pads to improve the environmental conditions for cows during periods of heat stress. Low profile cross-ventilated freestalls with evaporative pads (LPCV) have become a popular system. The purpose of this study was to evaluate how well these LPCV systems improve the temperature-humidity index (THI) under different ambient conditions. As ambient humidity increases, ability of the LPCV to reduce THI is decreased. Producers wishing to construct LPCV barns should carefully evaluate the climate in which they want to construct LPCV structures.
Dairy Research, 2007 is known as Dairy Day, 2007
Keywords: Dairy; THI; Heat stress; Cross ventilation; Temperature-humidity index